Mission Swachh Bharat: Stage is Set for Getting into Basics - Ranjan, Rakesh (Environment and urbanization Asia, 2014)
Launching of ‘Mission Swachh Bharat’—a time-bound programme for making India clean by 2 October 2019 by the federal government has been hailed by many as much needed intervention, even though city cleanliness is a municipal subject. However, for any cleanliness mission to succeed, its strategy needs to have three important elements: first, there is a need to constantly engage the citizenry. Second, it must have a strategy to reduce waste. Third, and quite importantly, success would critically depend on the improvement of processing of the waste. The paper argues that while the programme has been successfully launched as a mass movement with great deal of visibility, much is required to be done towards reducing and processing of waste. Unless this is done, our cities and towns may give a semblance of cleanliness, but they would continue to inflict incalculable damages to their surroundings. “Swachh Bharat 任务” 是一项设置了时间限制的工作，目的是在2019年10月2日前使印度变得清洁，虽然清洁问题是城市课题，联邦政府仍然提供了尽可能多的急需的干预。然而，对于任何想要取得成功的清洁任务来说，它的战略都应包括三个重要的要素：第一，有必要不断与公民建立紧密联系。其次，必须有减少废弃物的战略。第三，也是非常重要的，计划能否成功将主要取决于废弃物处理的工艺改进。本文认为，虽然任务作为一项具有较大知名度的群众运动已经成功推出，但在减少废弃物和处理加工方面需要更进一步的努力。除非做到这一点，不然我们的城市、城镇和村庄可能只是徒有清洁的外表，会继续对周围的环境造成难以估量的破坏。 本文不是有关卫生方面的技术文件。文中清楚地表明我们进行到何种阶段，面临着什么挑战，以及我们应该达到什么目标。尽管相关结果已经广为人知，本文的目的主要是研究在资金以及政治支持下我们为什么无法取得稳定的进展。为了明确这一原因，我们试图把讨论的主要关注点放在那些需要整理的议题上，从而为清洁问题制定一个可信的战略。 印度在废弃物管理方面存在着根深蒂固的偏见和管理体系上的缺陷，如果不解决这个问题，尽管拥有最好的意图和最高程度的资源，也无法产生一个最佳结果。这个问题开始于给卫生和供水设定一个比目前社会普遍水平高的标准。随着人们对市政服务的期望不断上升，城市政府面临着压力。与此同时，寻求解决城市基础设施不足的宏大而巧妙的技术解决方案已经使得许多城市政府变得盲目，他们应当在下水道、化粪池和固体废弃物管理方面寻找更便宜的和分散的解决方案。